Development of small cyclic peptides targeting the CK2α/β interface. Issue 30 (28th March 2022) - Atkinson, Eleanor L.; Iegre, Jessica; D'Amore, Claudio; Brear, Paul; Salvi, Mauro; Hyvönen, Marko; Spring, David R.
Abstract : Development of a small CK2α/β protein–protein interaction-inhibiting peptide, which is easily synthesisable and functionalisable, with good enzymatic and cellular activity. Abstract : In this work, an iterative cycle of enzymatic assays, X-ray crystallography, molecular modelling and cellular assays were used to develop a functionalisable chemical probe for the CK2α/β PPI. The lead peptide, P8C9, successfully binds to CK2α at the PPI site, is easily synthesisable and functionalisable, highly stable in serum and small enough to accommodate further optimisation.